Development of an Online Dietary Recall Tool Suitable for Use Among Ethnic Groups Living in Ireland: A Study Protocol. (7th June 2021) - Bennett, Grace; Yang, Shuhua; Bardon, Laura; Gibney, Eileen
Abstract: Objectives: To develop Foodbook24, an online dietary recall tool, for use among various population groups in Ireland and compare its use to traditional dietary recall methods Methods: The existing food list within Foodbook24 was expanded to include foods frequently consumed by Polish and Brazilian adults. Common foods consumed by the Irish population that were not included in the original food list were also added. The composition of foods per 100g, portion sizes and food portion images were collated for all additional foods. These data were retrieved from available national food composition and food consumption databases and other published sources. To test the completeness of the expanded food list n = 20 participants from each cohort (Irish, Polish, Brazilian) were recruited. Participants completed a personal reflection of their diet using a Pinterest Board of 30–40 images to represent foods they consume often, accompanied by an audio clip explaining food choices, eating patterns and how/where they prepare and serve their meals. Later participants completed two 24 hour dietary recalls using the modified Foodbook24 and an evaluation questionnaire to assess their likeability of the tool. A second cohort of n = 60 from each group were recruited to complete 24 hour dietary recalls using traditional interviewer led methods and Foodbook24, in a randomised manner, to test the comparability of food and nutrient intakes from each method Results: A total of 136 additional Irish, 26 Polish and 34 Brazilian foods were added to Foodbook24. Examination of participants' likeability and compatibility with the tool is ongoing. Food items commonly mentioned in the Pinterest study that are missing from the updated food list will be added and preliminary analysis on the 24 hour dietary recalls will be completed. Intakes recorded via interviewer led recalls and Foodbook24 will be compared and significant differences analysed to assess the compatibility of the updated Foodbook24 tool among populations in Ireland Conclusions: Food choice varies between population groups. The use of novel dietary assessment tools, such as Foodbook24, should be assessed among a diverse range of groups before it is deemed an accurate method of examining dietary intakes of an entire population. Funding Sources: Food Nutrition Security Cloud has received funding from the EU's Horizon 2020 Research and Innovation programme.